2018
DOI: 10.1002/pbc.27108
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ketamine + midazolam to propofol for procedural sedation for lumbar puncture in pediatric oncology by nonanesthesiologists—a randomized comparative trial

Abstract: Ketamine-midazolam combination is safer and more effective. Propofol is faster in onset and recovery, and has smoother emergence with poor efficacy at recommended initial doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Hypotension is likely the result of mild intravascular depletion secondary to prolonged state of fasting in combination with propofol's vasodilatory and myocardial depressant effects . Respiratory adverse events were not prominent in our study as reported in other studies . Propofol reduces airway muscle tone and protective airway reflexes may be reduced or eliminated.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Hypotension is likely the result of mild intravascular depletion secondary to prolonged state of fasting in combination with propofol's vasodilatory and myocardial depressant effects . Respiratory adverse events were not prominent in our study as reported in other studies . Propofol reduces airway muscle tone and protective airway reflexes may be reduced or eliminated.…”
Section: Discussionsupporting
confidence: 73%
“…Our study analysis revealed a significant decrease in the number of adverse events in the EMLA group (19%) as compared with the lidocaine group (41%). The incidence of adverse events reported in previous studies range from 28% to 56% in pediatric oncology patients receiving propofol to 13% to 52% in children receiving propofol with systemic and/or local analgesia for LPs and bone marrow procedures . A decrease in total propofol dose administered to the EMLA group in our study may have resulted in a reduction of the number of adverse events in this group.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…71 For sedation, ketamine is frequently combined with other agents like midazolam, propofol, and dexmedetomidine. 70,[72][73][74] Pellier et al prospectively evaluated a combination of midazolam (IV, 25 mcg/kg) and ketamine (IV, 0.5-2 mg/kg) for procedural sedation in children with cancer, and found it to be safe and effective. 75 Some of the undesirable adverse effects of IV ketamine used for sedation, such as hypersalivation and tachycardia, may be alleviated using atropine.…”
Section: Sedation and Procedural Painmentioning
confidence: 99%